Systematic status of Fejervarya ((Amphibia, Anura, Dicroglossidae) from South and SE Asia with the description of a new species from the Western Ghats of Peninsular India - Dinesh, K.p.; Vijayakumar, S.p.; Channakeshavamurthy, B.h.; Torsekar, Varun R.; Kulkarni, Nirmal U.; Shanker, Kartik (Zootaxa, 2015)
We carried out a large-scale phylogenetic analysis of fejervaryan (dicroglossid frogs with ’Fejervaryan lines’ on the ventral side of the body) frogs, distributed in South and SE Asia, using published and newly generated sequences of unidentified individuals from the northern Western Ghats. The results corroborate the presence of a larger fejervaryan clade with a sister relationship to a clade composed of Sphaerotheca. Two sister clades could be discerned within the lager fejervaryan clade. The unidentified individuals formed a monophyletic group and showed a strong support for a sister relationship with Minervarya sahyadris. The species was found to be highly divergent (16S rRNA–4% and tyr–1%) from its sister lineage Minervarya sahyadris, and the clade composed of these two lineages were found to be deeply nested within the larger clade of Fejervarya. Based on this, the genus Minervarya Dubois, Ohler and Biju, 2001 is synonymized under the genus Fejervarya Bolkay, 1915. The unidentified lineage is recognized, based on phylogenetic position, genetic divergence and morphological divergence, as a distinct species and named here as Fejervarya gomantaki sp. nov. The presence of rictal glands was observed to be a synapomorphic character shared by the nested clade members, Fejervarya sahyadris and Fejervarya gomantaki sp. nov. Based on the presence of rictal gland and small size, Minervarya chilapata, a species from a lowland region in the Eastern Himalayas, is synonymized under Fejervarya and evidence for morphological separation from the new species, Fejervarya gomantaki sp. nov. is provided. For the fejervaryan frogs, currently three generic names (Frost, 2015) are available for the two phylogenetic subclades; the genus Fejervarya Bolkay, 1915 for the species of fejervaryan frogs having distribution in the South East Asia; the genus Zakerana Howlader, 2011 for the species of fejervaryan frogs having distribution in the South Asia and the genus Minervarya Dubois, Ohler and Biju, 2001 nested within the ’Zakerana clade’. In the phylogenetic analysis Minervarya sahyadris, the new species described herein as Fejervarya gomantaki sp. nov. are nested within the ’Zakerana clade’, if the ’Zakerana clade’ for the fejervaryan frogs having distribution in the South Asia is provided a generic status the nomen ’Minervarya’ should be considered as per the principle of priority of the ICZN Code. Taking into consideration the overlapping distribution ranges of members of the sister clades within the larger fejervaryan clade and the absence of distinct morphological characteristics, we also synonymize the genus Zakerana Howlader, 2011, a name assigned to one of the sister clades with members predominantly distributed in South Asia, under the genus Fejervarya Bolkay, 1915. We discuss the need for additional sampling to identify additional taxa and determine the geographical ranges of the members of the sister clades within Fejervarya to resolve taxonomy within this group.